Branch and Bound Method in Determing Integer Linier Programming Solutions from UMKM Rendang Nan Lamak, Padang City - Alvin Ardiansyah Putra; Nurweni Putri; Iswan Rina; Aulia Oktavia (CIB Nusantara, 2025)
After Indonesia was hit by COVID-19 in 2019, it had an impact on the Indonesian economy. Many companies have closed and laid off employees (PHK), so the unemployment rate has increased. This event made people think creatively and innovatively by creating their own businesses to meet their daily needs. This has resulted in the emergence of many micro, small, and medium enterprises (UMKM) from various regions or cities, including the city of Padang. UMKM Rendang Nan Lamak is engaged in the food sector, namely processed rendang dishes. Especially for Rendang Nan Lamak, it serves several variants of rendang dishes, such as beef rendang, fern rendang, lokan rendang, and lokan fern rendang. The purpose of this research is to find out the maximum profit by using the Branch and Bound Method in determining Integer Linear Programming solutions from UMKM Rendang Nan Lamak.